1999
DOI: 10.1093/tropej/45.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Soil transmitted helminthic infection and its effect on nutritional status of adolescent schoolgirls of low socioeconomic status in Sri Lanka

Abstract: The prevalence of soil-transmitted helminthic infection, living conditions, and practices relating to personal hygiene were studied in schoolgirls (age 14-18 years) in both an urban area (n = 383) and a rural area (n = 231) of Sri Lanka. The impact of helminthic infection on nutritional status was also studied. The prevalence of Ascaris and Trichuris infection was significantly higher (p < 0.00001) in the urban area than in the rural area and this was associated with poor living conditions and personal hygiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
3
14
0
1
Order By: Relevance
“…9 In addition, Ascaris worms express a range of retinol binding proteins, retinol dehydrogenases, and retinoic acid receptors, which use retinol for growth and development, 22 although a study in Sri Lanka among adolescent girls found that Trichuris infection but not Ascaris infection was associated with lower serum vitamin A concentration compared with those girls not infected. 23 WHO and United Nations Children's Fund (UNICEF) have recommended that deworming be included in vitamin A supplementation programs, 24 and combined vitamin A supplementation and deworming have been shown to reduce Ascaris reinfection rates among PSC in Panama. 25 Although our results support an integrated approach, additional research is needed to elucidate the timing and duration of combined interventions with vitamin A and deworming.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, Ascaris worms express a range of retinol binding proteins, retinol dehydrogenases, and retinoic acid receptors, which use retinol for growth and development, 22 although a study in Sri Lanka among adolescent girls found that Trichuris infection but not Ascaris infection was associated with lower serum vitamin A concentration compared with those girls not infected. 23 WHO and United Nations Children's Fund (UNICEF) have recommended that deworming be included in vitamin A supplementation programs, 24 and combined vitamin A supplementation and deworming have been shown to reduce Ascaris reinfection rates among PSC in Panama. 25 Although our results support an integrated approach, additional research is needed to elucidate the timing and duration of combined interventions with vitamin A and deworming.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly due to poor community services that increase the likelihood of infections, our periurban slum dwellers had higher chances of being infected as compared to their urban counterparts. While living in rural area is significantly associated with highest infections (Escobedo et al 2008), poor living conditions and improper personal hygiene practices even in the urban areas have resulted in increased A. lumbricoides and T. trichiura infections (Atukorala and Lanerolle 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown a relatively high prevalence of handwashing after toileting and before meals among adolescents 18,21 . One study reported that frequent handwashing was related to toothbrushing 18 .…”
Section: Introductionmentioning
confidence: 90%